2014
DOI: 10.1007/s12010-014-0905-3
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Extent of Enzymatic Hydrolysis on Antioxidative Properties and ACE-Inhibitory Activities of Protein Hydrolysates from Goby (Zosterisessor ophiocephalus) Muscle

Abstract: Antioxidant properties and angiotensin-converting enzyme (ACE) inhibitory activities of protein hydrolysates from goby (Zosterisessor ophiocephalus) muscle, with different degrees of hydrolysis (DH) from 5 to 25%, prepared by treatment with crude proteases extract from smooth hound intestines, were investigated. Goby protein hydrolysates (GPHs) are rich in Gly and Thr, which accounted for 14.1-15% and 11.6-13.2% of the total amino acids, respectively. The antioxidant activities of GPHs were investigated by usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 50 publications
7
26
0
Order By: Relevance
“…The differences in DH values are essentially due to the difference in the specificity of enzymes used during hydrolysis. The shape of hydrolysis curves is similar to those previously published for hydrolysates from grass goby fish (Nasri et al 2014) and the press cake of horse mackerel (Garcia-Moreno et al 2014).…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…The differences in DH values are essentially due to the difference in the specificity of enzymes used during hydrolysis. The shape of hydrolysis curves is similar to those previously published for hydrolysates from grass goby fish (Nasri et al 2014) and the press cake of horse mackerel (Garcia-Moreno et al 2014).…”
Section: Resultssupporting
confidence: 84%
“…Peptides that are released in vivo from animal and plant proteins or consumed as hydrolysates, can be bioactive and have regulatory functions in humans beyond the normal and adequate nutrition (Korhonen and Pihlanto 2003). Depending on their structure, composition and sequence, these peptides may exhibit various bioactivities such as antioxidative, antihypertensive, cholesterol lowering, and antibacterial effects (Nasri et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gastrointestinal digestive proteases have often been used for production of bioactive peptides with ACE inhibitory activity (Lin et al 2012). Many studies have reported that low molecular weight peptides are better ACE inhibitors than high MW peptides (Raghavan and Kristinsson 2009;Barbana and Boye 2010;Nasri et al 2014). In the current study, the low molecular mass peptides present in the pepsin hydrolysate might have contributed to higher ACE inhibitory activity than trypsin hydrolysate (Chalamaiah et al 2013).…”
Section: Ace-inhibitory Activitymentioning
confidence: 99%
“…In the current study, the low molecular mass peptides present in the pepsin hydrolysate might have contributed to higher ACE inhibitory activity than trypsin hydrolysate (Chalamaiah et al 2013). In addition, the aromatic and hydrophobic amino acids present in the pepsin and trypsin hydrolysates play an important role in ACE inhibitory activity (Chalamaiah et al 2013;Lee et al 2011;Nasri et al 2014). The ACE inhibitory activity of rohu roe hydrolysates was lower than those of goby fish muscle protein hydrolysates and squid skin gelatin hydrolysates generated by gastrointestinal proteases (Nasri et al 2013a, b;Lin et al 2012), and but higher than that of tilapia protein hydrolysate fractions produced by cryotin and Flavourzyme (Raghavan and Kristinsson 2009).…”
Section: Ace-inhibitory Activitymentioning
confidence: 99%